Transparency-Based Management and Its Effect on Teacher Performance at Madrasah Tsanawiyah Negeri 9 Indramayu - Dirno Dirno; Abdus Salam; Abdul Karim; Uun Purnasih (Eduprof : Islamic Education Journal, 2026)
Managerial transparency has become one of the essential principles in the governance of modern educational institutions, including madrasahs. Despite its recognized importance, most existing studies focus on general school settings, leaving the specific dynamics of transparency practices in madrasah contexts underexplored. However, empirical studies examining the influence of management transparency on teacher performance within madrasah environments remain relatively limited. This study addresses this gap by situating transparency within the unique organizational and cultural characteristics of madrasahs. This study aims to analyze the effect of transparency-based management on teacher performance at Madrasah Tsanawiyah Negeri 9 Indramayu. The research employed a quantitative approach using a cross-sectional survey design. Data were collected through a Likert-scale questionnaire involving all permanent teachers as respondents (n = 30) using a total sampling technique. Because the sample consisted of only 30 teachers, the results cannot be widely generalized. Data analysis was conducted using descriptive statistics, validity and reliability tests, and simple linear regression with the assistance of SPSS software. The results indicate that the level of managerial transparency in the madrasah falls within the good category (M = 4.21; SD = 0.42), while teacher performance is categorized as very good (M = 4.33; SD = 0.38). Regression analysis shows that transparency-based management has a positive and significant effect on teacher performance (R = 0.723; R² = 0.523; p < 0.05). This finding indicates that approximately 52.3% of the variation in teacher performance in this study sample can be explained by management transparency practices, while the remaining proportion is influenced by other factors such as intrinsic motivation, the leadership of the madrasah principal, and workload. These results empirically demonstrate that transparency is not merely a procedural aspect of governance but a substantial predictor of teacher performance in faith-based educational institutions. These findings support organizational justice theory, which highlights the role of openness and clarity in building trust and commitment. Furthermore, this study extends the theory by illustrating how transparency operates within a madrasah setting, where formal administrative practices intersect with religious and social values. In madrasahs, managerial transparency functions not only as an administrative mechanism but also as a means to strengthen professional relationships between leaders and teachers. Thus, the study contributes conceptually by contextualizing organizational justice theory in Islamic educational institutions. This study concludes that transparency-based management can improve teacher performance and promote more accountable and participatory governance.